Single-molecule electronic devices come a step closer. (Research'eu results magazine)
The ever-increasing miniaturisation of electronic devices has spurred researchers to study conductors at the nano scale and find the thinnest wire imaginable : single molecules. EU scientists have demonstrated efficient current conduction in a molecular switch controlled by light and chemical stimuli.